Associations of Biomarkers of Inflammation and Breast Cancer in the Breast Adipose Tissue of Women with Combined Measures of Adiposity. (14th August 2021) - Chang, Sue-Ling; Tchernof, André; Durocher, Francine; Diorio, Caroline
Abstract : Background . Mechanisms underlying the obesity-breast cancer link involve inflammation but need to be elucidated. Determining obesity by combining body mass index (BMI) with the waist circumference (WC) may clarify the role of inflammatory and hormonally related markers in breast cancer. We examined the effect of combining adiposity indices (BMI/WC) with the gene expression of several biomarkers involved in breast cancer. Methods . Expression of cytochrome P450 family 19 subfamily A member 1 (CYP19A1), estrogen receptor-alpha (ER- α ), allograft inflammatory factor 1 (AIF1), cyclooxygenase-2 (COX2), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF- α ), and leptin (LEP) in 141 adipose breast tissues was quantified using qPCR method. BMI and WC were measured by a trained nurse and categorized using the median split, BMI LO WC LO, BMI LO WC HI, BMI HI WC LO, and BMI HI WC HI . Results . Gene expression of IL-6 (3-fold), TNF- α (2-fold), and LEP (2-fold) was higher in the breast adipose tissue of women with high WC regardless of BMI, that is, BMI LO WC HI and BMI HI WC HI women (all P  < 0.01). Compared to BMI LO WC LO women, gene expression of CYP19A1, COX2, and AIF1 was increased by two-fold in breast adipose tissue of BMI HI WC HI women (P  < 0.10). ER- α was not different across adiposity categories. Conclusions . The expression of some biomarkers, particularly those related to inflammation, is elevated in breast adipose tissue of women with a high WC independent of BMI. Obesity monitoring should also include women with normal or low BMI, but with central adiposity.